(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The term date rape refers to a form of acquaintance rape in which non-consensual sex takes place between two people in a dating relationship. Objective: The purpose of this research was to examine the frequency with which date rape incidents occur. Materials and Methods: Our hospital conducted a retrospective examination of all sexual assault allegations during a seven-year period, from 2016 to 2022. Date rape refers to any sexual assault while the victim and the perpetrator are or were in a romantic or intimate relationship. The police report, victim statement, and medical exam results were all thoroughly examined and studied. Result: Total of 187 claimed sexual assault cases were reported, out of which 7% were by date rape cases. 50% of the cases occurred in unknown places percentage of occurrence in hotels or dimly lit restaurants and house of a common friend are somewhat similar and are 22.2% and 27.8% respectively. Alcohol and drugs were used in 61.1% of incidents and in 23.5% of the cases suspected inhalational anesthetic agent was used. Conclusion: It's possible that underreporting is increasing the true incidence of such cases beyond what has been identified. Due to delays in reporting and sample collection, it was not possible to determine the precise drug or agent type utilised in several of the cases. Raising awareness about date rape amongst young women is crucial right now. It may be suggested that they exercise caution and stay away from potentially harmful foods and beverages.